Incidencia de la Participación Ciudadana en los Presupuestos Participativos del Gobierno Autónomo Descentralizado Parroquial de Tarqui, años 2019 al 2022 - Ramos Linares, César Eduardo (2024)
The analysis of the Participatory Budgets of the Decentralized Autonomous Government of Tarqui Parish, covering the years 2019 to 2022, reveals significant trends and patterns. This research aims to analyze the impact of Citizen Participation in the Participatory Budgets of the Decentralized Autonomous Government of Tarqui Parish for the years 2019 to 2023. The specific objectives include identifying the proposals and suggestions of citizen participation in the formulation of the Participatory Budgets of the Decentralized Autonomous Parish Government of Tarqui for the years 2019 to 2022, and formulating public policies for an effective exercise of citizen participation in the formulation of the Participatory Budgets of the Decentralized Autonomous Government of Tarqui Parish for the years 2019 to 2022. The research methodology aimed to explore the impact of citizen participation in the management of the Decentralized Autonomous Government (GAD) of Tarqui Parish during the period from 2019 to 2023. Various methods were employed, including deductive reasoning and bibliographic methods to locate relevant documents. Content analysis was used to examine public investment through participatory budgets, while the analytical method was employed to analyze the collected information and propose public policies. Recommendations focus on strengthening the active participation of the community, ensuring representativeness in meetings, improving transparency and documentation, and promoting joint evaluation between the Decentralized Autonomous Parish Government and the communities. .